To what extent error correction helps Advanced Intensive English II students to overcome their oral communication errors at the Foreign Language Department of the University Of El Salvador 2014 - Martínez de Morales, Ana Guadalupe; Canjura de Chávez, Silvia Raquel (2024)
The acquisition of English as a Second Language is a complex task which requires an important teachers' and students' effort. Through out the process of the second language acquisition, the students make different types of errors and it is the teachers’ duty to correct those errors in an appropriated manner. Therefore, it is fair to say that teachers perform errors correction every day in every single lesson and it is fundamental to know the impact that the teachers' feedback has on students' oral performance. Even though providing feedback is essential to help students to overcome their oral errors, at the beginning of the investigation the researchers thought that the students' oral performance could be hindered if they were wrongly corrected; however, the research showed results that may be surprising to the readers. In addition, to develop the investigation, the research paper was divided in seven chapters containing the following: statement of the problem on the first chapter which contains important information such as the description of the problem, the objectives of the research, the justification of the research, and more. The theoretical framework is on the second chapter, and this contains important aspects and theories related to the different existing error correction techniques. On chapter three it is the methodology, which describes the type of study used on the investigation, the research design, the universe and sample of the study, and the sample population. On chapter four it is shown the data gathering; on chapter five the data gathered is analyzed.